The Effect of Cigarette Smoking on Blood and Biochemical Parameters: A Comparative Study Among Male Smokers and Non-Smokers In Baghdad City - Jaafar, Noor Sadiq (Iraqi Journal of Science, 2020)
The impact of smoking on human health is remarkable and can lead to death. This research was performed to test the effects of cigarette smoking on some parameters that are considered as signs of critical problems in human body. The study was carried out on fifty Iraqi male smokers in Baghdad city, who smoked at least 10 cigarettes per day for at least 15 years. The group includes 25 male smokers with an age range of 20 -55 years and 25 male non-smokers who were collected with the same range of age for statistical comparison. The results of the study revealed significant increases in blood parameters, including hemoglobin (Hb, 16.0917 (g/dl) , packed cell volume (PCV, 49.2%), red blood cells (RBC, 5.4763 X1012/L), white blood cell (WBC, 12.5565 X109/L), and platelet (PLT, 430.000 x1012/L). Similar effects were observed in relation to the serum biochemical parameters o of kidney function (urea, 53.2400 mg/ dl; creatinine, 1.5480 mg/ dl) as well as liver function (alanine aminotransferase, ALT, 104.9200 U/l; aspartate transaminase, AST, 122.3040 U/l; alkaline phosphatase, ALP, 337.4000U/l); total serum bilirubin, TSB, 0.6780 mg/ dl). However, significantly decreased levels of total protein (60.6800 mg/ dl) and uric acid (4.2400 mg/ dl) were recorded in cigarette smokers when compared with non-smokers group.